New Pathogens in Blood Donors and Patients in Albania - Irena Seferi; Viola Shano; Brunilda Dakavelli; Vjollca Duro; Shpetim Qyra; Anyla Bulo (Albanian Journal of Trauma and Emergency Surgery)
Introduction: The emergence of novel pathogens poses a significant and immediate threat to global blood safety, particularly in regions experiencing epidemiological shifts. This study urgently examines the prevalence and impact of newly identified pathogens among blood donors and recipients in Albania, focusing on assessing their implications for public health and transfusion medicine.